On Kinetics of Upgrading Reactions by Supercritical Water Technology of Highly Sour Qayara Crude Oil over an Activated Carbon-Based Catalyst - Gheni, Saba A.; Mohammed, Mohammed H.; Hamad, Khaleel I.; hmood, Hassan M. (Journal of Petroleum Research and Studies, 2023)
Currently clean energy and zero emission fuel is a priority as there is a growing level of pollutants in air, sea and soil. Also, the conventional Iraqi crude oil is going to deplete according to the statistical analysis. Thus, methods of upgrading should attract attention in Iraqi fuel sector. The method of supercritical fluids (SCF) is one of the advanced approaches to upgrade the unconventional crude oil and removal of high levels of sulfur compounds. The present work aims at developing a kinetic model for upgrading reactions by supercritical water technology of a sour Iraqi crude oil. This aim was achieved via conducting sets of experiments in a hydrothermal autoclave reactor over a cobalt/activated carbon catalyst. The AC was used as a support for Co as an active metal. A set of upgrading kinetics experiments were applied at different temperatures (290-350 °C) and reaction times (0-45 min). Upon evaluation of the prepared catalysts for kinetics of upgrading by supercritical water technology, it was found that the process flows pseudo first order mechanism. Also, the activation energy of the chemical reaction was found to be 204.1 kJ/mol which is much less compared to previous studies